2019
DOI: 10.1080/08039488.2019.1646804
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in older adults with ADHD: links to ADHD symptom levels and executive functioning deficits

Abstract: Purpose and aim: The overall aim of the present study was to examine quality of life in attention deficit hyperactivity disorder (ADHD) patients age !60 years. First, we compared older adults with ADHD to both healthy controls of the same age and younger adults with ADHD. Second, we examined executive functioning as a possible underlying factor for quality of life among older adults with ADHD. Methods: The study included 158 participants in three groups: (1) older adults (60-75 years of age) with ADHD (n ¼ 42)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 34 publications
4
25
0
1
Order By: Relevance
“…26,60,61 Otras investigaciones señalan que el deterioro cognitivo con que cursan los adultos con TEA, tiende a incrementar su severidad cuando este trastorno del neurodesarrollo concomita con sintomatología neuropsiquiátrica como la depresión y la ansiedad. [62][63][64][65][66] Caselli et al (2018) 59 analizaron el fenotipo del TEA en población adulta y su correlación con el deterioro cognitivo subjetivo. Los hallazgos indican que el deterioro cognitivo subjetivo fue una queja frecuente en los sujetos, y que tras un seguimiento de 10 años un 7.9% del total de evaluados evolucionaron a un deterioro cognitivo patológico, dentro de los cuales 8.9% correspondía a sujetos con características fenotípicas de TEA versus el 7.8% reportado en sujetos sin estas características.…”
Section: Deterioro Cognitivo Y Teaunclassified
“…26,60,61 Otras investigaciones señalan que el deterioro cognitivo con que cursan los adultos con TEA, tiende a incrementar su severidad cuando este trastorno del neurodesarrollo concomita con sintomatología neuropsiquiátrica como la depresión y la ansiedad. [62][63][64][65][66] Caselli et al (2018) 59 analizaron el fenotipo del TEA en población adulta y su correlación con el deterioro cognitivo subjetivo. Los hallazgos indican que el deterioro cognitivo subjetivo fue una queja frecuente en los sujetos, y que tras un seguimiento de 10 años un 7.9% del total de evaluados evolucionaron a un deterioro cognitivo patológico, dentro de los cuales 8.9% correspondía a sujetos con características fenotípicas de TEA versus el 7.8% reportado en sujetos sin estas características.…”
Section: Deterioro Cognitivo Y Teaunclassified
“…If neuropsychological deficits are found to be related to daily life functioning beyond the influence of ADHD symptom levels, this may help us better determine which specific mechanisms are related to various outcomes in daily life. When controlling for ADHD symptom levels, self-ratings of inhibition and self-organization/planning have been shown to be related to overall impairment (Barkley & Fischer, 2011), and self-rated executive deficits have been shown to be related to quality of life (Stern et al, 2017;Thorell, Holst, & Sj€ owall, 2019). In addition, a few studies have shown that ADHD patients with executive deficits have more problems in daily life functioning with regard to unemployment, academic achievement, and criminality compared to ADHD patients without these deficits (Holst & Thorell, in press).…”
Section: Neuropsychological Deficits Daily Life Functioning and Quamentioning
confidence: 99%
“…ADHD has a negative impact on daily life functions such as impaired academic, occupational, and social functions (Thorell et al, 2019). Children with ADHD experienced academic failure, peer rejection, loss of self-esteem, loss of motivation, and helplessness of learning, unfocused, defiant, destructive, tireless, aimlessly clear, and nosy (Leung, et.al, 1994).…”
Section: Introductionmentioning
confidence: 99%